The Model M Method and Its Contribution to a Socially Responsible Society - Hrast, Anita; Mulej, Matjaž (Naše gospodarstvo/Our economy, 2020)
Model M means being young and being a role model for others in finding innovative employment or creating one’s own employment, and thus becoming and remaining an active citizen. In years 2012-2018, IRDO – Institute for the Development of Social Responsibility – implemented the project Model M Slovenia. The project started in the Podravje region, in years 2012-2014, with a small amount of money invested by the local community (The City Municipality of Maribor). Later (in years 2016-2018), it became a nation-wide Slovenian project funded by the EU’s Social Fund and the Republic of Slovenia. The purpose of the project was to empower youth with training, networking, counselling and active participation in the society to create their own models of success. In this paper, we present the Model M method (MMm) that we have developed through the Model M Slovenia project and its social impact on the employment of youth in Slovenia. With the Social Return on Investment (SROI), a method for social impact measurement, we present how the funds invested in the local pilot project were later multiplied tenfold on a national level within the project Model M Slovenia. The originality of the MMm, as presented in this paper, is in its requisitely holistic approach to youth training in terms of personal and social responsibility. The MMm is accelerating the (self)employment of youth and other unemployed persons. The MMm was created by a team of business practitioners and social responsibility researchers. Their aim was to practice and develop social responsibility, interdependence and requisitely holistic approach as a systemic behaviour, suggested by the global humankind in the ISO 26000 guidance standard.